West facing elevation of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the west-facing elevation of the Bhandasar Temple. The exterior walls of the temple are divided into five bays, of which the central bay is wider than the two bays flanking it on either side. The doorways of these walls when open, make the interiors of the temple semi-open and light up the interiors. The blind foliated arches of each bay have rectangular patterns that might have had paintings at some point but at present, only the outlines of these rectangles survive. At the centre of the plinth, there is a small chhatri (memorial) which was probably added to the temple later.